2021
DOI: 10.1093/ibd/izab110
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Biosimilar Utilization at a Pediatric Inflammatory Bowel Disease Center and Associated Cost Savings: Show Me the Money

Abstract: Background Tumor necrosis factor-alpha inhibitors (anti-TNFs) are a primary treatment for inflammatory bowel disease. Pharmaceutical expenditures and usage of specialty drugs are increasing. In the United States, biosimilars continue to be underutilized, despite opportunities for health care cost savings. Through quality improvement (QI) methodology, we aimed to increase biosimilar utilization among eligible patients initiating intravenous (IV) anti-TNF therapy and describe patient outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…The percentages on the far right (in light gray) are a sum of those that rated the question as strongly agree and agree. pediatric patients about biosimilars (10). This initiative increased the utilization of IV anti-TNF biosimilars from 1% at baseline to 96% among patients previously naïve to anti-TNF therapy and we have shown sustained improvement.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The percentages on the far right (in light gray) are a sum of those that rated the question as strongly agree and agree. pediatric patients about biosimilars (10). This initiative increased the utilization of IV anti-TNF biosimilars from 1% at baseline to 96% among patients previously naïve to anti-TNF therapy and we have shown sustained improvement.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, it highlights the need to educate patients and their caregivers on the efficacy and safety of biosimilars, especially as non-medical switches are becoming more common by insurance companies and due to majority of patients and caregivers having no prior knowledge of biosimilars. Quality improvement strategies have shown to be effective at improving education amongst pediatric patients and their caregivers about biosimilars before therapy initiation (10). Caregivers that have previously heard of biosimilars will require reeducation on the safety and efficacy of biosimilars in order to impact their negative perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient education is also an important aspect of the acceptance of biosimilar treatment. Morris et al 60 have recently demonstrated the successful application of a quality improvement approach to boost biosimilar use from 1% to 96% in intravenous anti-TNF-α naïve pediatric patients. This was achieved through substantial provider and patient education and expediting the prior authorization process for all inpatient and outpatient biosimilar starters.…”
Section: Knowledge On Biosimilar Usementioning
confidence: 99%